Economic globalization and labor rights: a disaggregated analysis - Peksen, Dursun (Human rights review, 2021)
Does economic globalization create a “race to the bottom” or a “race to the top” in labor rights practices? Despite significant research on the possible impact of economic globalization on labor conditions, little consensus exists as to whether and what forms of economic openness might help or undermine labor rights. In this study, we illustrate the significance of considering the two distinct processes of de facto and de jure globalization. We argue that whereas de facto globalization in the form of trade and financial transactions is likely to result in worse labor rights practices, de jure globalization that entails regulations to facilitate these transactions is likely to have a positive effect on labor conditions. Combining time-series, cross-national data on labor rights with data on economic globalization, we find significant evidence of the divergent effects of de facto and de jure globalization on labor rights practices. Results also indicate that the labor rights effects of de facto and de jure globalization are stronger for trade than financial globalization. We further show that the effects of economic globalization apply to both collective and substantive labor rights practices.